Retrospective review of profile of intensive care unit admissions and outcomes in a tertiary care hospital of Himalayan region - Khanduri, Sushant; Katiyar, Sonika; Kishore, Nand; Sodhi, Rakhee; Aggarwal, Ankit (International Journal of Research in Medical Sciences, 2017)
Background: An Intensive care unit (ICU) is an area where highest level of care is given with close invasive and non-invasive monitoring to a critically ill patient. Medical audit is must to assess the quality care provided and lay down policies for future. Objectives: To review retrospectively the profile of patients admitted to ICU and assess their outcome. Methods: From January 2016 to December 2016, ICU records of all admissions, referred, discharges, and deaths were utilized for the purpose of this study. Data extracted from the records included age, sex, diagnosis and outcome. Results: A total of 2316 patients were admitted to ICU. Males were 1489 (64.3%) and females were 827 (35.7%). Most of the patients (42.8%) were between 46-70 years. Most of the patients were shifted from emergency (48.5%) and it was associated with better outcome. A total of 49.6% patients were shifted out of ICU in stable condition while mortality was 28.6%. Around 21.8% patients left ICU against Medical advice. Conclusions: Majority patients admitted to ICU were of general medicine and neurosurgery. Survival was inversely related to age. Mortality was not associated with sex. Outcome was also related to the source from where patient was admitted.